Legal Compliance of Physiotherapists to Professional Competency Standards: A Case Study at Bintang Physio and Physiozone Physiotherapy Practices in Bandung - Dwi Panulat, Pandu; Andasari, Ririn; Prabaningtyas, Ayu Rizki; Zahid Abdillah, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2025)
Intoduction: The physiotherapy profession plays a critical role in the healthcare system, particularly in improving physical function and patient recovery. However, challenges persist regarding the compliance of physiotherapists with legal and professional competency standards. Objective: This study aims to analyze the legal compliance of physiotherapists with the established professional competency standards at two private physiotherapy practices in Bandung: Bintang Physio and Physiozone. Method: A qualitative research approach was used, employing purposive sampling to select 10 participants, including physiotherapists and clinic managers. Data were collected through in-depth interviews, field observations, and document analysis. Result and Discussion: The results revealed that physiotherapists at both clinics generally adhered to legal requirements, including the possession of valid Surat Tanda Registrasi (STR) and Surat Izin Praktik (SIP). Furthermore, both clinics followed standardized operating procedures (SOPs) and maintained ethical conduct in their professional interactions. However, challenges such as economic pressures and market demands were identified as potential barriers to full compliance. Conclusion: In conclusion, while legal compliance is largely met in both clinics, ongoing support and education are necessary to address existing barriers and enhance adherence to professional standards